2022
DOI: 10.1111/wej.12771
|View full text |Cite
|
Sign up to set email alerts
|

Fungus‐based bioremediation of olive mill wastewater and potential use in horticulture

Abstract: Proposed treatment processes of OMWW have not been efficient in decreasing its high toxicity or lowering its ecological impact. Bioremediation using microorganisms might be considered an environmentally friendly alternative. In this work, four fungal isolates were tested for their efficacy in lowering the toxicity of OMWW. Results of this work showed that fungal isolates were able to grow on OMWW. However, only one isolate (OMWW2) showed significant lowering in total phenols from 159.27 mg/ml (in controlled un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…endophyte yeasts that clustered together with the RODW isolates provides ground to speculate that the indigenous Cyberlindnera yeasts which inhabit the distillation facilities could originate from rose flower endophytes brought with the rose flowers and adapted to the discharged phenolic-rich wastewater. Similar scenarios of the spontaneous fermentation of plant phenolic-rich products and aqueous mixtures by indigenous yeasts were reported for other plant processing industries as well, such as the spontaneous grape must fermentation by indigenous yeasts inhabiting the winery and vineyards [ 12 , 13 , 24 ], and the spontaneous fermentation of cocoa pulp [ 14 ], olive mill wastewater [ 7 , 10 , 11 ], coffee processing wastes [ 25 ], tea [ 26 ] and others [ 16 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…endophyte yeasts that clustered together with the RODW isolates provides ground to speculate that the indigenous Cyberlindnera yeasts which inhabit the distillation facilities could originate from rose flower endophytes brought with the rose flowers and adapted to the discharged phenolic-rich wastewater. Similar scenarios of the spontaneous fermentation of plant phenolic-rich products and aqueous mixtures by indigenous yeasts were reported for other plant processing industries as well, such as the spontaneous grape must fermentation by indigenous yeasts inhabiting the winery and vineyards [ 12 , 13 , 24 ], and the spontaneous fermentation of cocoa pulp [ 14 ], olive mill wastewater [ 7 , 10 , 11 ], coffee processing wastes [ 25 ], tea [ 26 ] and others [ 16 ].…”
Section: Discussionmentioning
confidence: 60%
“…So far, bacterial, yeast and fungal fermentation have been successfully applied to the biotransformation and bioremediation of phenolic-rich wastewater from various sources and with various compositions. A notable example is the olive mill wastewater, which has been a subject of directional phenolic modifications and/or degradation via various microbial fermentations and treatments [ 7 , 8 , 9 , 10 , 11 ]. Indigenous yeasts and molds inhabiting the production sites relating to the processing of phenolic-rich plant products and their associated wastes offer a valuable source for the selection of isolates with a high fermentation capacity for phenolic-rich plant products and wastewater [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the benefits of fungi to degrade phenolic compounds from the olive mill wastewater [20][21][22]. These fungi produce highly oxidative enzymes, such as ligninase and laccase, to degrade recalcitrant organic molecules, in particular the phenolic bound molecules [23].…”
Section: Introductionmentioning
confidence: 99%